An Analysis of the Globalization Impact on Food Supply Adequacy in Selected Developing Countries - Alforque, Juliana; Buot, Dhymae Marl; Crampatanta, Charlywin; Paporo, Mohammad Hanif; Laygan, Resa Mae; Abing, Martha Joy; Capulong, Charlyn; Teves, Maria Rizalia (AGRARIS: Journal of Agribusiness and Rural Development Research, 2025)
Despite ongoing efforts to reduce hunger, inadequate food supply remains a perilous issue in developing countries. The State of Food Security and Nutrition in the World 2024 report highlights the rising incidence of severe food insecurity, particularly in developing countries, and the worsening conditions in nations already experiencing significant hardship. Accordingly, this study aims to assess the role of globalization in addressing food supply adequacy in developing nations. It focused on answering the research gap on whether globalization significantly affects food security. The research utilized data from 80 developing countries from 2012 to 2021. Employing panel-corrected standard error (PCSE) estimation with 800 observations, the analysis revealed that globalization exerted a positive and statistically significant impact on food supply adequacy. A gain of one point in the globalization index enhanced food supply adequacy, all else being equal. Social globalization, political globalization, economically active age group population, and access to finance and financial products for farmers favorably influenced food supply adequacy; however, the World Risk Index (WRI) imposed an adverse impact. Additionally, economic globalization exhibited a detrimental and substantial effect, whereas agricultural total factor productivity demonstrated a positive association lacking statistical significance. These discoveries suggested that globalization enhanced food supply adequacy, emphasizing the necessity for governments in developing countries to adopt policies fostering economic integration and invest in resilient food systems to ensure an adequate food supply.